KEMAMPUAN METAKOGNITIF SISWA SMP DALAM MENYELESAIKAN SOAL SISTEM PERSAMAAN LINEAR DUA VARIABEL - Aulia Sinta Dewi; Fatqurhohman Fatqurhohman; Yoga Dwi Windy Kusuma Ningtyas (SIGMA, 2023)
The purpose of this research is to describe the metacognitive abilities of class VIII students in solving problems in SPLDV material. This type of research uses descriptive qualitative. Data collection techniques used written tests and semi-structured interviews as subjects of the study in class VIII C students located at SMPN 2 Wuluhan, Jember Regency. Subject data obtained 3 categories of metacognitive abilities which include, categories of high metacognitive abilities, categories of moderate metacognitive abilities, and categories of low metacognitive abilities. The categories of high metacognitive abilities include awareness activities, regulatory activities, and evaluation activities. In the category of moderate metacognitive abilities, there are awareness activities although they are not complete, there are regulatory activities although some do not use a planning strategy, and there are also evaluation activities although some have not been completed in problem solving. In the category of low metacognitive abilities, there are awareness activities, although some do not write completely, there are regulatory activities, although only a few solve questions without a planning strategy, and there is no evaluation activity.